Diversity and Eco-Evolutionary Associations of Endosymbiotic Astome Ciliates With Their Lumbricid Earthworm Hosts - Obert, Tomáš; Rurik, Ivan; Vd’ačný, Peter (Frontiers in Microbiology, 2021)
Coevolution of endosymbionts with their hosts plays an important role in the processes of speciation and is among the most fascinating topics in evolutionary biology. Astome ciliates represent an interesting model for coevolutionary studies because they are so tightly associated with their host organisms that they completely lost the cell oral apparatus. In the present study, we used five nuclear markers (18S rRNA gene, ITS1-5.8S-ITS2 region, and 28S rRNA gene) and two mitochondrial genes (16S rRNA gene and cytochrome c oxidase subunit I) to explore the diversity of astomes inhabiting the digestive tract of lumbricid earthworms at temperate latitudes in Central Europe and to cast more light on their host specificity and coevolution events that shaped their diversification. The present coevolutionary and phylogenetic interaction-adjusted similarity analyses suggested that almost every host switch leads to speciation and firm association with the new host. Nevertheless, the suggested high structural host specificity of astomes needs to be tested with increased earthworm sampling, as only 52 out of 735 lumbricid earthworms (7.07%) were inhabited by ciliates. On the other hand, the diversification of astomes associated with megascolecid and glossoscolecid earthworms might have been driven by duplication events without host switching.